Modeling in TRNSYS of a single effect evaporation system powered by a Rankine cycle - Casimiro, Sergio (2012)
The paper presents an analysis of a Single Effect Evaporation (SEE) system as a pre-study to the feasibility of concentrated solar power plants (CSP) powering desalination units for cogeneration of water and electricity. An algorithm to model a SEE system in steady-state operation was made and is described in this work. This algorithm was implemented in TRNSYS environment, and a simple analysis was conducted of a SEE system powered by a Rankine cycle used in CSP plants.